Chapter 1 Racial and Ethnic Diversity in the Performing Arts Workforce - Stein, Tobie S. (Taylor & Francis, 2019)
Racial and Ethnic Diversity in the Performing Arts Workforce examines the systemic and institutional barriers and individual biases that continue to perpetuate a predominately White nonprofit performing arts workforce in the United States. Workforce diversity, for purposes of this book, is defined as racial and ethnic diversity among workforce participants and stakeholders in the performing arts, including employees, artists, board members, funders, donors, educators, audience, and community members. The research explicitly uncovers the sociological and psychological reasons for inequitable workforce policies and practices within the historically White nonprofit performing arts sector, and provides examples of the ways in which transformative leaders, sharing a multiplicity of cultural backgrounds, can collaboratively and collectively create and produce a culturally plural community-centered workforce in the performing arts.